Polskojęzyczny słownik terminologii ogólnometaglottodydaktycznej jako narzędzie mediacji wewnątrzdyscyplinowej - Bigoraj, Izabela (Neofilolog, 2026)
In this article, we present a preliminary reflection on our idea of developing a Polish-language dictionary of general meta-glottodidactic terminology as a tool for intradisciplinary mediation. Such a representation of knowledge in contemporary glottodidactics would serve to systematize and organize the field and could, in our opinion, support scholars’ (meta)cognitive and communicative activity, thereby facilitating specialized communication between glottodidacticians. In the first part of the article, we define the concept of intradisciplinary mediation from the perspective of specialized scientific dialogue between glottodidacticians and justify the need to develop a dictionary of general meta-glottodidactic terminology as a tool for this type of mediation. We then analyze the definitions of the term “glottodidactics” provided in Aleksander Szulc’s Dictionary of foreign language didactics and in already existing Polish-language glossaries containing general (meta)glottodidactic terms. We also propose our own definition, which takes into account various approaches to the scientific nature of glottodidactics and to its subject matter. In our view, such a definition would be useful in intradisciplinary mediation, because its function would be to make researchers aware of the diversity of ways of understanding and practicing language teaching within the framework of a scientific discipline. It would also contain information about the epistemological foundations of these differences. The article concludes by formulating concrete objectives that could guide further work on our dictionary project and its implementation.